Pengaruh Serial Bodyweight Squat Terhadap Tinggi Lompatan Vertikal Pada Mahasiswa Laki-Laki Fakultas Kedokteran Universitas Sam Ratulangi - Alverdo Waraney Nathanael Gerung; Fransiska Lintong; Jimmy Franky Rumampuk (Journal of Comprehensive Science, 2026)
Vertical jump is one of the important physical abilities that reflects the explosive power of the lower leg muscles, so it is often used to assess functional performance and explosive movement capacity. This ability is influenced by muscle strength and movement coordination. Bodyweight squats are a simple, easy-to-do exercise that has the potential to increase muscle strength and explosive ability without requiring additional equipment, making it relevant for students who generally have varied and limited physical activity. The purpose of this study was to determine the effect of serial bodyweight squats on vertical jump height in male students at the Faculty of Medicine, Sam Ratulangi University. A quasi-experimental study with a one-group pretest–posttest design was conducted to compare the results before and after the intervention, which were then analyzed using the Wilcoxon nonparametric test. Measurements of vertical jump height before and after a 4-week intervention on 44 subjects showed an increase in vertical jump height with a significance value of 0.000 (p<0.05). There is an effect of serial bodyweight squat training on vertical jump height in students.